Cone beam computed tomography analysis of the edentulous mandibular symphysis - Mense, Chloë (J Dent Sci, 2021)
BACKGROUND/PURPOSE: Overdenture with single symphyseal implant is one of the useful clinical approach for elderly edentulous patients. We aimed to evaluate edentulous patients with regards to the relationship between dimensions, bone characteristics, cancellous densities, and cortical thickness of the mandibular symphyseal region using cone beam computed tomography (CBCT). MATERIAL AND METHODS: We analyzed 103 CBCT from pre-implant investigations. All included patients were healthy without any disorders affecting bone metabolism. We performed 13 measurements for each patient: 9 of height, width, and thickness (mm) and 4 of density (Hounsfield Units; HU). Fisher's exact test was applied to examine the association between two categorical variables, the Pearson correlation coefficient to measure the strength of linear relationship between two quantitative variables. We used the two-sample Student's t-test to compare mean symphysis height between men and women, the paired Student's t-test to compare mean lingual and buccal cortical thickness. For all tests, the threshold of significance was fixed at 5%. RESULTS: Men and women significantly differed with regards to mean total symphysis height (p = 0.004) and the distribution of Cawood and Howell classifications (p = 0.033). Symphysis height was negatively correlated with mean density of cancellous bone (r = −0.453, p < 0.001). Mean lingual cortical thickness significantly differed from mean vestibular thickness (p < 0.001, paired Student's t-test). CONCLUSION: Present findings supported that symphyseal measurements are parameters that reflect the symphysis bone characteristics, and can guide the choice of a suitable implant design.